Functional profiling of a human cytomegalovirus genome - Dunn, Walter (National Academy of Sciences, 2003)
Human cytomegalovirus (HCMV), a ubiquitous herpesvirus, causes a lifelong subclinical infection in healthy adults but leads to significant morbidity and mortality in neonates and immunocompromised individuals. Its ability to grow in different cell types is responsible for HCMV-associated diseases, including mental retardation and retinitis, and vascular disorders. To globally assess viral gene function for replication in cells, we determined the genomic sequence of a bacterial artificial chromosome (BAC)-based clone of HCMV Towne strain and used this information to delete each of its 162 unique ORFs and generate a collection of viral mutants. The growth of these mutants in different cultured cells was examined to systematically investigate the necessity of each ORF for replication. Our results showed that 45 ORFs are essential for viral replication in fibroblasts and 117 are nonessential. Some genes were found to be required for viral replication in retinal pigment epithelial cells and microvascular endothelial cells, but not in fibroblasts, indicating their role as tropism factors. Interestingly, several viral mutants grew 10- to 500-fold better than the parental strain in different cell types, suggesting that the deleted ORFs encode replication temperance or repressing functions. Thus, HCMV encodes supportive and suppressive growth regulators for optimizing its replication in human fibroblasts, epithelial, and endothelial cells. Suppression of viral replication by virus-encoded temperance factors represents a novel mechanism for regulating the growth of an animal virus, and may contribute to HCMV's optimal infection of different tissues and successful proliferation among the human population.